DEVELOPMENT GUIDED INQUIRY-BASED FLIPPED CLASSROOM LEARNING SYSTEM FOR INDUSTRIAL REVOLUTION 4.0 ERA ON CHEMICAL BONDING MATERIAL USING LMS MOODLE - Dian Pratiwi; Mawardi Mawardi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
Characterization of education in the 4.0 industrial revolution era uses digital technology in learning. Therefore, this study aims to develop a guided inquiry-based flipped classroom learning system using LMS Moodle on chemistry class X SMA/MA and to determine the level of validity and practicality of the product developed. The results of processing the validity test data are 0.88, which indicates a valid category. While the results of processing the practicality test data with an average of 89% for students categorized as very practical and an average of 94% practicality for teachers with very practical categories. Overall, the study results indicate that the guided inquiry-based flipped classroom learning system using LMS moodle on chemical bonding material for class X SMA/MA is valid and practical.